Mitochondrial and redox modifications in early stages of Huntington's disease - Carla Lopes; I. Luísa Ferreira; Carina Maranga; Margarida Beatriz; Sandra I. Mota; José Sereno; João Castelhano; Antero Abrunhosa; Francisco Oliveira; Maura De Rosa; Michael Hayden; Mário N. Laço; et al. (Redox Biology, 2022)
Deficits in mitochondrial function and redox deregulation have been attributed to Huntington's disease (HD), a genetic neurodegenerative disorder largely affecting the striatum. However, whether these changes occur in early stages of the disease and can be detected in vivo is still unclear. In the present study, we analysed changes in mitochondrial function and production of reactive oxygen species (ROS) at early stages and with disease progression. Studies were performed in vivo in human brain by PET using [64Cu]-ATSM and ex vivo in human skin fibroblasts of premanifest and prodromal (Pre-M) and manifest HD carriers. In vivo brain [64Cu]-ATSM PET in YAC128 transgenic mouse and striatal and cortical isolated mitochondria were assessed at presymptomatic (3 month-old, mo) and symptomatic (6–12 mo) stages. Pre-M HD carriers exhibited enhanced whole-brain (with exception of caudate) [64Cu]-ATSM labelling, correlating with CAG repeat number. Fibroblasts from Pre-M showed enhanced basal and maximal respiration, proton leak and increased hydrogen peroxide (H2O2) levels, later progressing in manifest HD. Mitochondria from fibroblasts of Pre-M HD carriers also showed reduced circularity, while higher number of mitochondrial DNA copies correlated with maximal respiratory capacity. In vivo animal PET analysis showed increased accumulation of [64Cu]-ATSM in YAC128 mouse striatum. YAC128 mouse (at 3 months) striatal isolated mitochondria exhibited a rise in basal and maximal mitochondrial respiration and in ATP production, and increased complex II and III activities. YAC128 mouse striatal mitochondria also showed enhanced mitochondrial H2O2 levels and circularity, revealed by brain ultrastructure analysis, and defects in Ca2+ handling, supporting increased striatal susceptibility. Data demonstrate both human and mouse mitochondrial overactivity and altered morphology at early HD stages, facilitating redox unbalance, the latter progressing with manifest disease.